Cholelithiasis: WES Sign - Hamid Ehsani-Nia; Shannon Toohey (Journal of Education and Teaching in Emergency Medicine, 2017)
History of present illness: A 33-year-old female with multiple previous episodes of biliary colic presented to the emergency department with severe right upper quadrant pain that started 30 minutes prior to arrival. She characterized her pain as sharp and pulling and radiating to the back. Upon physical examination, patient was in acute distress with severe tenderness to right upper quadrant palpation. Her abdomen was soft, with no guarding or rebound tenderness.